Comparison of Diagnostic Methods in Detection of Squamous Cell Abnormalities in Iranian Women with Abnormal Pap's Smear Test and Associated Demographic and Issues - Fatemeh Samiee Rad; mehdi Ghaebi; Simin Zarabadipour; Arezoo Bajelan; fatemeh Pashazade; Mehri Kalhor; Amane Barikani (Iranian Society of Pathology, 2020)
Background & Objective: Premalignant lesions of cervix have increased dramatically in recent years. Early diagnosis and management of abnormalities have an effective role in preventing the invasion of the disease and also in timely treatment. This study aimed to compare diagnostic methods in the detection of squamous cell abnormalities with abnormal Pap smear test. Methods: This cross-sectional study was performed on 1000 women with abnormal Pap smears in 2007-2018. Sampling was performed with simple method. All samples were subjected to an immediate assessment of colposcopy and histopathology if suspected. The checklist included demographic information as well as symptoms, cytopathology, colposcopy and histopathology findings. Data analysis was performed using descriptive and statistical analysis (P<0.05). Result: A significant relationship between histopathology and Pap smear findings was found (P=0.009), also there was a significant correlation between histopathology and colposcopy findings (P=0.001). However, there was no significant relationship between clinical symptoms and histopathology findings (p=0.8). Sensitivity , specificity , positive and  negative predictive value of Pap smear were 43%, 65.9%, 75.4%, 32.2% and of colposcopy were 74.7%, 39.5%, 75%, 39.1%, and of clinical symptoms were 72.6%, 28.1%, 71.1%, 29.7%, respectively. Conclusion: Pap smear findings have the appropriate diagnostic accuracy in comparison with colposcopy and histopathology findings for screening and diagnosis of squamous intra-epithelial lesions. Also, there was higher sensitivity of colposcopy compared with Pap smear to detect cervical lesions. Therefore, it is advisable to use these methods simultaneously.